EFFECT OF FEED QUANTUM DURING FIFTH AGE SILKWORM, BOMBYX MORI L. ON REELING PARAMETERS - BORA, BHADRAM; MAHADEVAMURTHY, T. S.; SHIVAKUMAR, G. R.; MAGAIDUM, S. B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1995)
The effect of differentfeed quantum (18 to 32 feeds) during 5th instar of PMX NB4D2 and NB4D2x NB7 was studied. The larvae have been starved after 16 feeds (4th day) during 5th instar are unable to spin cocoons. The larvae starved after 18 feed have spun lighter cocoons. The quality of the cocoons were inferior upto 24 feeding level and the quality of silk was superior in 26 to 28 feeding level. The present study indicates that 26 to 28 feed level yield better reeling characters.